2019
DOI: 10.3389/fphar.2019.00463
|View full text |Cite
|
Sign up to set email alerts
|

miR-155 in the Resolution of Atherosclerosis

Abstract: Atherosclerosis is a chronic progressive inflammatory disease where advanced lesions can eventually completely obstruct blood flow resulting in clinical events, such as a myocardial infarction or stroke. Monocytes and macrophages are the dominant biologically active immune cells involved in atherosclerosis disease and play a pivotal role during initiation, progression, and regression of disease. Altering macrophage inflammation is critical to induce regression of atherosclerosis and microRNAs (miRs) have emerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(50 citation statements)
references
References 80 publications
1
47
0
Order By: Relevance
“…Finally, our results also showed an increase of miR‐155 in NLSDM patients in comparison to the control group. MiR‐155 has important functions in inflammation and, recently, was described to contribute to liver pathology and arteriosclerosis …”
Section: Discussionmentioning
confidence: 99%
“…Finally, our results also showed an increase of miR‐155 in NLSDM patients in comparison to the control group. MiR‐155 has important functions in inflammation and, recently, was described to contribute to liver pathology and arteriosclerosis …”
Section: Discussionmentioning
confidence: 99%
“…Li et al [33] suggested that the increased level of miR-155 could relieve inflammation and foam cell formation via the signaling pathway of miR-155-CARHSP1-TNF-α, but it was also claimed that the anti-inflammatory function of HDL is conferred through miRNA-33. Besides, miR-33 inhibition in macrophages has been verified to be able to enhance cholesterol efflux and reduce As lesions in mice [32] . Additionally, miR-21, a pro-survival gene for VSMCs, is another important miRNA in As, which has been demonstrated to be capable of impacting neointimal formation [28] .…”
Section: Mirnas In Atherosclerosis (As)mentioning
confidence: 99%
“…Recently, multiple studies have reported that miRNAs are dysregulated during the development of As ( Table 2), for example, several miRNAs such as miR-155, miR-33 are upregulated in As [30,32] . Considering the function of miRNAs in macrophage polarization, they may be able to serve as important regulators and predictors for As.…”
Section: Mirnas In Atherosclerosis (As)mentioning
confidence: 99%
See 2 more Smart Citations